Efektifitas Pendampingan Kelompok Wanita Tani oleh Balai Penyuluh Pertanian di Kota Metro - Munawaroh, Imroatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to evaluate the effectiveness of the assistance provided by the Agricultural Extension Center (Balai Penyuluh Pertanian/BPP) to Women Farmer Groups (Kelompok Wanita Tani/KWT) in Metro City in promoting economic self-reliance and household-based environmental management. The central issue examined is the extent to which BPP’s interventions, through technical training and participatory facilitation, enhance the capacity of KWT members to transform household waste into organic fertilizer and to develop sustainable home gardening practices. Using a descriptive qualitative approach, this research explores the mentoring activities related to organic fertilizer production, yard utilization, and the planning of fish-and-vegetable bucket cultivation (budikdamber). The findings indicate that BPP’s assistance significantly contributes to improving members’ technical skills, ecological awareness, and social solidarity in managing local resources. The innovations produced include solid and liquid organic fertilizers, optimized household-scale gardening, and the initiation of budikdamber practices. These results reinforce participatory development and gender-based community empowerment theories while enriching the literature on urban agroecology in Muslim urban settings. The novelty of this study lies in the integration of technical and social approaches in women-centered agricultural mentoring that responds to issues of food security and domestic waste management. This article offers a collaborative mentoring model that can be replicated in other urban-periurban areas with similar social characteristics.